THE ANALGESIC EFFECT AND IMPROVEMENT OF DAILY LIVING FUNCTION OF TAM TY TANG COMBINED WITH SPINAL TRACTION IN THE TREATMENT OF LUMBAR-HIP SYNDROME AT THAI BINH TRADITIONAL MEDICINE HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: Assessment of the analgesic effect and improvement of daily living function of Tam ty tang combined with spinal traction in the treatment of lumbar-hip syndrome due to spinal degeneration.Subjects and methods: Clinical intervention research, prospective, comparing before and after treatment. 60 patients in the research group used Tam ty tang combined with spinal traction.Results: After 20 days of treatment, the mean VAS pain score decreased from 5.63 ± 1.08 points to 1.27 ± 0.86 points, a statistically significant difference (p < 0.05); the mean daily living function score (ODI score) decreased from 13.67 ± 1.10 points to 6.10 ± 1.12 points, a statistically significant improvement (p < 0.05).Conclusion: Tam ty tang combined with spinal traction has an analgesic effect and improves daily living function in the treatment of lumbar-hip syndrome due to spinal degeneration.
Keywords: Tam ty tang combined, spinal traction, lumbar-hip syndrome, spinal degeneration.